Terapia da bota de unna na redução do edema em portadores de lesão venosa - Cardoso, Luciana Ventura (2018)
Venous insufficiency is linked to longevity; an aggravating factor worldwidely, its main complication is venous ulcer. The boot of Unna is one of the forms of compression therapy. The bioimpedanciometry investigates accurately the patient's water balance. Objective: To evaluate the lower limb edema during the day comparing the use of the Unna’s boot and the conventional dressing through bioimpedanciometry. Material and Method: Fifteen legs with active wounds were evaluated, from September 2014 to December 2016. Randomization was drawing and the statistical analysis was performed using the paired t test, considering an alpha error of 5%. Results: The female representation was 100% of the total participants, the age ranged from 50 to 76 years, a mean age was 63 years. A significant difference between volume variations between morning and afternoon was found among those who did not wear the Unna’s boot. When compared the difference of edema with and without the Unna’s boot, it was detected that without the Unna’s boot the edema volume was higher. Conclusion: Unna’s boot showed better results than conventional dressing in relation to the reduction of lower limb edema during the day in patients with chronic venous ulcer.